Diagnostic approach and genetic diversity of jackfruit bronzing bacterium in Malaysia - Abidin, Nuraizat; Mohamed Zulperi, Dzarifah; Ismail, Siti Izera; Yusof, Mohd Termizi; Ismail Suhaimy, Noor Wahida; Karam Singh, Daljit Singh; Awang @ Mansor, Mohd Hakiman (Academic Journals, 2018)
A serious problem faced in the jack fruit industry in Malaysia caused by bronzing disease by pathogen Pantoea stewartii subspe. stewartii (P. stewartii subsp. stewartii ) as it reduces the quality of the fresh jack fruit, hence, affects the consumer preference towards the fruits. It is important to keep the fruit healthy as it provides revenue to the local and export markets in Malaysia. This review aimes to present an overview and diagnostic approach of jackfruit bronzing disease in Malaysia. Detection and identification methods following past and recent study of the causal pathogen via phenotypic identification, molecular identification, pathogenicity test, genetic relationship and genetic diversity. Successful detection and identification were obtained with appropriate phenotypic tests performed and molecular identification using CPSL1/CPSR2c primers and ES16/ESIG2c primers. Pantoea stewartii subsp. stewartii strains were also pathogenic to healthy detached and attached jack fruit and the high liability of the phylogenetic and clustering analyses in the causal pathogen via multilocus sequencing analysis (MLSA) of the partial nucleotide sequences of the genes gyrB, rpoB, atpD and infB, using a bootstrap analysis with 1000 replicates on the individual and concatenated peptide sequence trees. The presented review provides an overview on bronzing disease of jackfruit in Malaysia, the appropriate detection, identification, pathogenicity of its causal pathogen and the application of multilocus sequence analysis (MLSA) as the best tool to study the pathogen diversity and evolution. Up to now, little information and studies have been done on bronzing disease of jackfruit and its causal agent, P. stewartii subsp. stewartii in Malaysia.